Asbestos-related lung disease: An update - Schuhmann, M.; Brims, Fraser; O'Reilly, K. (2011)
In this work, we describe both benign and malignant asbestos-related diseases and provide an updated review of recent advances in the field. It has long been appreciated that the inhalation of asbestos fibers causes several well-described respiratory diseases including pleural plaques, diffuse pleural thickening, asbestosis, lung cancer, and malignant pleural mesothelioma (MPM). However, despite this knowledge and stricter industrial controls, the incidence of these diseases continues to increase in many parts of the world. In fact, despite the introduction of strict limits early in the 20th century, the mortality rate due to MPM is still increasing in industrialized countries such as the United Kingdom and Australia. In this update we provide an overview of each disease entity while concentrating on the role that newer imaging techniques, including high-resolution computed tomography, magnetic resonance imaging, and positron emission tomography /computed tomography, play in the diagnosis of asbestos-related pleural and parenchymal diseases. As the incidence of MPM continues to increase in many parts of the world, this review also focuses on new approaches to the diagnosis and treatment of this devastating condition. A description of the potential use and limitations of biomarkers in the diagnosis and monitoring of the disease is included along with recent trial data examining novel vaccine-based biological therapies. © 2011 by Lippincott Williams & Wilkins.